Analisis Proses Manajemen Kaderisasi Intra Kampus dalam Pembentukan Karakter Kepemimpinan Mahasiswa Keperawatan - Yongki Hendro; Iyos Sutresna; Heri Ridwan (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
The formation of leadership character with integrity and competence is a primary demand in nursing education. The intra-campus cadreization process managed through POAC functions (Planning, Organizing, Actuating, Controlling) is expected to be an effective vehicle for shaping such character. However, academic constraints and execution inconsistencies often pose challenges. This study aims to analyze the relationship between the intra-campus cadreization management process and the formation of nursing student leadership character. This study employed a descriptive correlational design with a cross-sectional approach. The sample consisted of 120 nursing students from the class of 2024, selected using total sampling technique. The instruments used were valid and reliable questionnaires on cadreization management and leadership character. Data analysis was performed using univariate and bivariate Spearman Rank tests. The results showed that the cadreization management process was perceived as effective by the majority of respondents (61.7%), and student leadership character was in the strong category (61.7%), with Moral Feeling as the highest aspect. Statistical tests revealed a significant positive relationship between cadreization management and leadership character (p-value = 0.001), although the correlation strength was weak (r = 0.394). Dimensional analysis indicated that Organizing had the strongest relationship, while Controlling had the weakest. In conclusion, cadreization management contributes positively to leadership character formation but is not the sole determinant factor. It is recommended that student organizations prioritize empowering organizing approaches over strict controlling to optimize character building.